2015
DOI: 10.1021/acs.analchem.5b01377
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Host Cell Protein Analysis Using Two Dimensional Data Independent LC–MSE

Abstract: Host cell proteins (HCPs) are bioprocess-related impurities arising from cell-death or secretion from nonhuman cells used for recombinant protein production. Clearance of HCPs through downstream purification (DSP) is required to produce safe and efficacious therapeutic proteins. While traditionally measured using anti-HCP ELISA, more in-depth approaches for HCP characterization may ensure that risks to patients from HCPs are adequately assessed. Mass spectrometry methods provide rationale for targeted removal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 31 publications
4
62
0
Order By: Relevance
“…For proteomics screening of cells and their conditioned media a high pH/low pH reversed phase 2D‐nano‐LC − MS E method was used which includes label‐free Hi3 quantitation and was previously introduced and validated for the determination of HCPs in purified mAb samples (Doneanu et al, ; Farrell et al, ; Silva et al, ; Silva, Gorenstein, Li, Vissers, & Geromanos, ). MS E is a multiplexed data independent acquisition mode.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For proteomics screening of cells and their conditioned media a high pH/low pH reversed phase 2D‐nano‐LC − MS E method was used which includes label‐free Hi3 quantitation and was previously introduced and validated for the determination of HCPs in purified mAb samples (Doneanu et al, ; Farrell et al, ; Silva et al, ; Silva, Gorenstein, Li, Vissers, & Geromanos, ). MS E is a multiplexed data independent acquisition mode.…”
Section: Resultsmentioning
confidence: 99%
“…LC‐MS based “omics”‐approaches are increasingly used to gain advanced understanding of biomanufacturing processes such as to study host cell proteins (HCPs), productivity during process scale‐up or cellular response to altered media composition (Farrell et al, ; Gao et al, ; Liu et al, ). The recent elucidation of the CHO cellular and secreted proteome further facilitates research in this area (Baycin‐Hizal et al, ; Kumar et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…One DIA method, 19 MS E , has been coupled with two dimensional liquid chromatography (2D-LC) to identify and quantify low abundance HCPs, using the "Top 3 00 label-free approach (MS signal response for the three most intense tryptic peptides) for protein quantitation. 7,8,10,20,21 However, 2D-LC analysis may have reproducibility challenges and the nano-LC often used in the second dimension for improved sensitivity is not always robust. In addition, its 10-20 hours analysis time/sample makes it challenging to analyze multiple samples from in-process pools using the 2D-LC-MS/MS approach to provide real time support and quick response for addressing potential HCP concerns.…”
Section: Introductionmentioning
confidence: 99%
“…As part of an effort to help users understand the conditions under which 2D-LC provides more resolving power than 1D-LC separations for peptide analyses, the Heinisch group recently demonstrated that the peak capacity of 2D-LC separations is superior to that of 1D-LC separations for analysis times longer than about five minutes [18]. In the area of Host Cell Protein (HCP) analysis, Donenau and coworkers have demonstrated the use of heartcutting 2D-LC [19,20] and offline comprehensive 2D-LC [21] to detect trace-level peptide markers of HCPs. This is very important to quality assurance for biotherapeutic mAbs.…”
Section: Peptide Level Analysismentioning
confidence: 99%